2020
DOI: 10.1001/jamapediatrics.2020.0932
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Specificity of Pediatric Health Policy Discussions in Political Campaigns

Abstract: Well-designed public policy can promote health among children, 1-3 but there is reason to worry that pediatric health issues may get crowded out of policy discussions and debates. Politicians are incentivized to craft their health care policies around the interests of voting-age citizens, and politicians are unlikely to see children as important drivers of health care spending. 1,4 To assess the national political profile of pediatric health issues, we analyzed a database of Congressional candidate campaign we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…In the Finnish context, we are aware of previous studies that have assessed the extent to which children are represented in municipal council discussions [21], newspapers and in election studies [22]. Our findings are in line with the US study by Benning et al, showing that children are not central to election discussions [4]. We are unaware of other studies in the Nordic countries or from similar socioeconomic contexts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the Finnish context, we are aware of previous studies that have assessed the extent to which children are represented in municipal council discussions [21], newspapers and in election studies [22]. Our findings are in line with the US study by Benning et al, showing that children are not central to election discussions [4]. We are unaware of other studies in the Nordic countries or from similar socioeconomic contexts.…”
Section: Discussionsupporting
confidence: 86%
“…The role of children and their wellbeing is, basically, undocumented in terms of election themes. In the US context, a study by Benning et al found that children’s health-related issues were rarely mentioned in the US Congressional candidate’s campaign websites [4]. In the Finnish context, we are unaware of any study examining the role of children in election discussions.…”
Section: Introductionmentioning
confidence: 99%
“…As officeholders also have a great influence in directing and implementing the MH promotion-related activities of the municipality, it should be ensured that they develop effective and long-term policies that address children’s health needs. However, previous studies have found that children and families with children are poorly reflected in political discourse and goal setting ( Benning et al , 2020 ; Hiilamo et al , 2021 ; Pereira et al , 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…Very few Democratic Congressional campaign websites discuss pediatric health policies; even fewer Republican ones do. 1 It is troubling that candidates would neglect issues directly affecting the current and future health and well-being of more than 73 million Americans-more than one-fifth of the US population. 2,3 Worse, child health can be indirectly impacted by adult-focused policies, but this issue is often considered after the fact.…”
mentioning
confidence: 99%
“…Because children do not vote, are disproportionately poor and disenfranchised, and usually incur lower health care costs than older adults, their health issues are given less attention in public policy debates. Very few Democratic Congressional campaign websites discuss pediatric health policies; even fewer Republican ones do …”
mentioning
confidence: 99%